Antibody-Mediated Inhibition of Insulin-Degrading Enzyme Improves Insulin Activity in a Diabetic Mouse Model - Fursht, Ofir; Liran, Mirit; Nash, Yuval; Medala, Vijay Krishna; Ini, Dor; Royal, Tabitha Grace; Goldsmith, Guy; Nahary, Limor; Benhar, Itai; Frenkel, Dan (Frontiers in Immunology, 2022)
Diabetes is a metabolic disease that may lead to different life-threatening complications. While insulin constitutes a beneficial treatment, it’s use may be limited due to increased degradation and an increase of side effects such as weight gain and hypoglycemia. Small molecule inhibitors to insulin-degrading enzyme (IDE) have been previously suggested as a potential treatment for diabetes through their ability to reduce insulin degradation and thus increase insulin activity. Nevertheless, their tendency to bind to the zinc ion in the catalytic site of IDE may affect other important metalloproteases and limit their clinical use. Here, we describe the isolation of IDE-specific antibody that specifically inhibits insulin degradation by IDE. Using phage display, we generated a human IDE-specific antibody that binds human and mouse IDE with high affinity and specificity and can differentiate between active IDE to a mutated IDE with reduced catalytic activity in the range of 1 nM. We further assessed the ability of that IDE-inhibiting antibody to improve insulin activity in vivo in an STZ-induced diabetes mouse model. Since human antibodies may stimulate the mouse immune response to generate anti-human antibodies, we reformatted our inhibitory antibody to a “reverse chimeric” antibody that maintained the ability to inhibit IDE in vitro, but consisted of mouse constant regions, for reduced immunogenicity. We discovered that one intraperitoneal (IP) administration of the IDE-specific antibody in STZ-induced diabetic mice improved insulin activity in an insulin tolerance test (ITT) assay and reduced blood glucose levels. Our results suggest that antibody-mediated inhibition of IDE may be beneficial on improving insulin activity in a diabetic environment.